Fear of the Monsters in H.P. Lovecraft’s Short Stories “Whisperer in the Darkness” (1930) & “At the Mountain of Madness” (1931): Freudian Psychology of the Uncanny - Titis Tri Ningtyas; Ali Mustofa (Journal of English Language Studies, 2022)
An encounter with ominous objects or situations that causes one to feel uneasy, frightening, or afraid is known as an uncanny experience. It involves both feelings and situations that make someone uneasy. This article focused on the uncanny feelings in Lovecraft's two well-known short stories, "At the Mountain of Madness" (1930) and "Whisperer in the Darkness" (1931). By employing Sigmund Freud's psychological notion of "the uncanny", the study revealed that the uncanny attracts to readers in a variety of ways. They are simple overriding ideas that have been imprinted in the character's long-suppressed memories and are reinforced by the monstrosity's appearance. It focuses on both the monster's incredible physical characteristics and the characters' insanity or fear as a result of their unconsciousness. Their reality is broken, and the characters are unaware of the condition of the item as a result, supporting Freud's theories on repressed memories in the unconscious that emerge as a psychological defense mechanism.